The Development of Fake News in the Post-Truth Age - Muqsith, Munadhil Abdul; Pratomo, Rizky Ridho (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
This study aims to provide a complete picture of the development of fake news during this post-truth era. Authors use a qualitative approach with a literature study method. Today's society uses social media for various needs and has considerable advantages. However, social media is also a mouthpiece for spreading fake news. Fake news today is a threat to society. In the post-truth era, people only believe in the truth of news based on belief, not objective facts. Society becomes polarized because of a relative definition of truth. This phenomenon is also supported by an algorithm that causes people to echo their own making. It is this echo that makes objective facts blurry and causes truth bias. Plus, with the development of technology, it is possible to make videos that resemble the original or deep fakes. Deep fakes become dangerous because people are becoming increasingly difficult to distinguish whether a video is real or fake. Many applications are able to create deep fakes video. This study concludes that fake news in this era is becoming increasingly dangerous. However, the public also plays a role in accelerating the development of fake news. Literacy skills, such as digital literacy, are very important to prevent the harmful effects of fake news.Keywords: Fake News; Digital Literacy; Deepfake; Post-TruthÂ AbstrakPenelitian ini bertujuan untuk memberikan gambaran yang utuh tentang perkembangan berita palsu di era post-truth ini. Penulis menggunakan pendekatan kualitatif dengan metode studi literatur. Masyarakat saat ini menggunakan media sosial untuk berbagai kebutuhan dan memiliki keuntungan yang cukup besar. Namun, media sosial juga menjadi corong penyebaran berita bohong. Berita palsu hari ini adalah ancaman bagi masyarakat. Di era post-truth, orang hanya percaya pada kebenaran berita berdasarkan keyakinan, bukan fakta objektif. Masyarakat menjadi terpolarisasi karena definisi kebenaran yang relatif. Fenomena ini juga didukung oleh algoritma yang menyebabkan orang menggemakan buatan mereka sendiri. Gema inilah yang membuat fakta objektif menjadi kabur dan menyebabkan bias kebenaran. Ditambah lagi dengan perkembangan teknologi yang memungkinkan untuk membuat video yang menyerupai aslinya atau deep fakes. Kepalsuan yang dalam menjadi berbahaya karena orang semakin sulit membedakan apakah video itu asli atau palsu. Banyak aplikasi yang mampu membuat video palsu yang dalam. Studi ini menyimpulkan bahwa berita palsu di era ini semakin berbahaya. Namun, masyarakat juga berperan dalam mempercepat berkembangnya berita bohong. Keterampilan literasi, seperti literasi digital, sangat penting untuk mencegah efek berbahaya dari berita palsu.Kata Kunci: Berita Palsu; Literasi Digital; Palsu; Pasca-Kebenaran